2019
DOI: 10.1007/978-3-030-29414-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Estimation-of-Distribution Algorithms

Abstract: Estimation-of-distribution algorithms (EDAs) are general metaheuristics used in optimization that represent a more recent alternative to classical approaches like evolutionary algorithms. In a nutshell, EDAs typically do not directly evolve populations of search points but build probabilistic models of promising solutions by repeatedly sampling and selecting points from the underlying search space. Recently, there has been made significant progress in the theoretical understanding of EDAs. This article provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 55 publications
(143 reference statements)
0
31
0
Order By: Relevance
“…Costa, Jones, and Kroese [2] proved that a constant smoothing parameter for the Cross Entropy (CE) algorithm (which is equivalent to a constant learning rate ρ for PBIL) results in that the probability mass function converges to a unit mass at some random candidate, but no convergence speed analysis was given. In summary, as Krejca and Witt said in [10], the genetic drift in EDAs is a general problem of martingales, that is, that a random process with zero expected change will eventually stop at the absorbing boundaries of the range. Results of Witt [16] and Lengler, Sudholt, and Witt [13] as well as the two works by Lehre and Nguyen [12] and by Doerr and GECCO '20 Companion, July 8-12, 2020, Cancún, Mexico Benjamin Doerr and Weijie Zheng Krejca [3] showed that genetic drift can result in a considerable performance loss.…”
Section: Summary Of Our Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Costa, Jones, and Kroese [2] proved that a constant smoothing parameter for the Cross Entropy (CE) algorithm (which is equivalent to a constant learning rate ρ for PBIL) results in that the probability mass function converges to a unit mass at some random candidate, but no convergence speed analysis was given. In summary, as Krejca and Witt said in [10], the genetic drift in EDAs is a general problem of martingales, that is, that a random process with zero expected change will eventually stop at the absorbing boundaries of the range. Results of Witt [16] and Lengler, Sudholt, and Witt [13] as well as the two works by Lehre and Nguyen [12] and by Doerr and GECCO '20 Companion, July 8-12, 2020, Cancún, Mexico Benjamin Doerr and Weijie Zheng Krejca [3] showed that genetic drift can result in a considerable performance loss.…”
Section: Summary Of Our Resultsmentioning
confidence: 97%
“…Since almost all theoretical results for EDAs regard univariate models [10], this paper deals exclusively with univariate EDAs, that is, the bit positions of the probabilistic model are mutually independent. Univariate EDAs include Population-Based Incremental Learning (PBIL) with special cases Univariate Marginal Distribution Algorithm (UMDA) and Max-Min Ant System with iteration-best update, and the Compact Genetic Algorithm (cGA).…”
Section: Summary Of Our Resultsmentioning
confidence: 99%
“…Theoretical analyses of EDAs also often suggest an advantage of EDAs when compared to evolutionary algorithms (EAs); for an in-depth survey of run time results for EDAs, please refer to the article by Krejca and Witt (2020). With respect to simple unimodal functions, EDAs seem to be comparable to EAs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, design hybrid methods that combine metaheuristics and local search are highly needed to obtain practical efficient solvers [25][26][27]. Estimation of Distribution Algorithms (EDAs) are promising metaheuristics-in which exploration for potential solutions in search space depends on building and sampling explicit probabilistic models of promising candidates' solutions [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%